Fine Coal Dry Cleaning using an Air Dense Medium Fluidized Bed with Improved Magnetite Medium. (2015) - Zhao, Yuemin; Fu, Zhijie; Yang, Xuliang; Luo, Zhenfu; Duan, Chenglong; Song, Shulei; Cai, Luhui
Abstract: Coal beneficiation using air dense medium fluidized bed offers a number of advantages and provides an efficient solution for coal cleaning in a dry way. Recently, the development of the air dense medium fluidized bed mainly concentrate on the coarse coal (+6 mm), and it is also reported that fine coal (-6 mm) is hard to be separated by conventional magnetite medium. The objective of this study is to using four types of magnetite powders with different narrow size range to separate -6+3 mm fine coal. The pressure-drop performance of the different magnetite medium in fluidized bed was also experimentally studied. The results show that the finer magnetite powders have a lower pressure-drop and minimum fluidization velocity than the coarse magnetite powders, and the -6+3 mm fine coal can be separated effectively by -0.15+0.074 mm magnetite powders, which will expand the lower separation limit of the air dense medium fluidized bed.